A substrate integrated waveguide based dual‐band leaky‐wave antenna fed by TE10 and TE20 modes. Issue 6 (29th March 2022) - Wei, Dujuan; Geng, Youlin; Zhang, Pengquan; Zhang, Zhonghai; Yin, Chuan; Du, Tiejun; Zhang, Wei
Abstract: A dual‐band leaky wave antenna (LWA) based on substrate integrated waveguide (SIW) is presented in this paper. The radiation elements are composed of a set of periodical transverse slots and a long longitudinal slot that can radiate scanning beams at two different bands under TE10 ‐mode and TE20 ‐mode excitation, respectively. The scanning beams in the two bands both cover the forward region, and polarizations are perpendicular. Under TE10 excitation, the proposed antenna radiates scanning beams in the low band (8.2 GHz 9.1 GHz) with gain varying from 10.6 to 15.9 dBi. Under TE20 excitation, the beams of the proposed antenna scan in the high band of 18.8 GHz 22 GHz with gain varying in 11.7 dBi 16 dBi. The measured results of the fabricated prototype confirm the design theory and simulated results.